2020
DOI: 10.1136/bmj.m1361
|View full text |Cite
|
Sign up to set email alerts
|

Progression to type 2 diabetes in women with a known history of gestational diabetes: systematic review and meta-analysis

Abstract: ObjectiveTo estimate and compare progression rates to type 2 diabetes mellitus (T2DM) in women with gestational diabetes mellitus (GDM) and healthy controls.DesignSystematic review and meta-analysis.Data sourcesMedline and Embase between January 2000 and December 2019, studies published in English and conducted on humans.Eligibility criteria for selecting studiesObservational studies investigating progression to T2DM. Inclusion criteria were postpartum follow-up for at least 12 months, incident physician based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
476
3
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(581 citation statements)
references
References 54 publications
12
476
3
23
Order By: Relevance
“…Women with GDM are at higher risk of pre-eclampsia, more likely to have their labour induced and to give birth by caesarean section than women without GDM [ 4 ]. Their lifetime risk for developing type 2 diabetes and cardiovascular disease is high [ 5 , 6 ]. Infants born to women with GDM are more likely to be LGA than infants born to women without GDM, with increased risk of an operative birth, birth injuries, and significant neonatal morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with GDM are at higher risk of pre-eclampsia, more likely to have their labour induced and to give birth by caesarean section than women without GDM [ 4 ]. Their lifetime risk for developing type 2 diabetes and cardiovascular disease is high [ 5 , 6 ]. Infants born to women with GDM are more likely to be LGA than infants born to women without GDM, with increased risk of an operative birth, birth injuries, and significant neonatal morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a major and increasing health problem worldwide with rates varying depending on the population and diagnostic criteria used [ 1 , 2 ]. Defined by the World Health Organisation as “carbohydrate intolerance resulting in hyperglycaemia with onset or first recognition during pregnancy” [ 3 ], GDM has immediate health risks for the women and her offspring [ 4 ] as well as lifelong implications for their health [ 5 , 6 ], with adverse health effects continuing into the next generation [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reports are in line with our ndings. In the other hand, many previous systematic review and metaanalysis as well as cohort studies reported that higher FBG levels could increase the risk of GDM and type 2 diabetes in later life [47][48][49][50][51]. Therefore, higher preconception exposure to PMs might increase the risk of type 2 diabetes in these participants in later life.…”
Section: Available Evidencementioning
confidence: 96%
“…In recent decades, the prevalence of GDM has increased by more than 30% in several countries, including developing countries [ 6 , 7 ]. Women with a history of GDM have a 9-fold increased risk of developing future T2DM [ 8 ].…”
Section: Introductionmentioning
confidence: 99%